Me siento parte de mi Familia - Rodrguez Noriega, Adriana Michelle (2018)
The work of professional proficiency had the title "I feel part of my family", whose development of the learning session has been based on bibliographical references and other sources of consultation, as well as with the application of knowledge acquired in the academic years of my life vocational training. My conclusions summarize that: the end of the family is not only to meet the social, economic and spiritual needs of the adolescent, but also that he feels an important part of his family, regardless of the type of constitution he may have, supporting the time your self-esteem._x000D_ The competence developed in the present class corresponds to "Build your Identity", in which students must be recognized as a member of a specific sociocultural community and have a sense of permanence to their family._x000D_ The didactic processes allow organizing better the learning of the students, organizing their knowledge in an orderly manner. The interaction between the teacher and the student allows integration between the whole classrooms, being recommendable the images.